Prophylactic Phenobarbital after Resolution of Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The degree of practice variation in continuance of phenobarbital treatment despite resolution of neonatal seizures was evaluated by national survey conducted at the University of Rochester Medical Center, New York.